HUMAN DIGNITY. LEGAL AND PHILOSOPHICAL PERSPECTIVE - Elżbieta A. Maj (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
The article is an attempt to find answers to the question of the guarantee of respect for human dignity in statutory law. The analysis refers to natural law, personalism, morality, law and the principles of citizenship, in order to highlight the dignity inherent to man as a natural and positive value.